BVOCs and global change - Peñuelas, Josep; Staudt, Michael (Trends in plant science, 2010)
Biogenic volatile organic compounds (BVOCs) produced by plants are involved in plant growth, reproduction and defense. They are emitted from vegetation into the atmosphere and have significant effects on other organisms and on atmospheric chemistry and physics. Here, we review current knowledge on the alteration of BVOC emission rates due to climate and global changes: warming, drought, land use changes, high atmospheric CO 2 concentrations, ozone and enhanced UV radiation. These alterations are very variable depending on the doses, timing, BVOC and species, but in overall terms are likely to increase BVOC emissions. These changed emissions can lead to unforeseeable consequences for the biosphere structure and functioning, and can disturb biosphere feedback on atmospheric chemistry and climate with a direction and intensity that warrants in-depth investigation.